Pembinaan masyarakat desa untuk peningkatan pendapatan melalui teknologi budidaya kepiting soka di Desa Pulau Cawan Kecamatan Mandah Kabupaten Indragiri Hilir - T Ersti Yulika Sari; Usman Usman; Niken Ayu Pramungkas; Mulyadi Idris; Sumarto Sumarto; Eni Yulinda; Ridar Henrik (Unri Conference Series: Community Engagement, 2019)
Soft-shelled crabs are mangrove crabs that are cultivated and harvested while moulting so that their shells are soft and easy to consume. The purpose of this activity is to increase the income of the people of Pulau Cawan Village, Mandah District, Indragiri Hilir Regency through the cultivation of soft-shelled crabs. by introducing environmentally friendly cultivation techniques, but can produce added value in terms of improving the family's economy through soft-shelled crab cultivation. Training on softwater crab cultivation techniques and training in the construction of aquaculture ponds (crabs box). These community service activities are carried out using several approach methods, namely providing understanding to the community carried out in the form of FGD (Focus Group Discussion), as well as conducting discussions and practice on crab cultivation to dig up information about understanding environmentally friendly cultivation, protect mangrove ecosystems, increase household income through adding value to catches and solutions regarding fishermen from outside the village who use destructive fishing, by giving poison. A series of services activities conducted on soft shell crab farming techniques (shelled) can be received well by the crab catch fisherman in Desa Pulau Cawan. Increased knowledge and skills of crab catch fishermen in the cultivation of soft shell crabs placed in crab boxes can provide provisions so that these farming activities can continue, and Desa Cawan Island can become a pilot village for soft shell crab cultivation techniques for the next few years.